2016
DOI: 10.17344/acsi.2016.2289
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Diquinone and Dihydroquinone Derivatives of Calix[4]arene and Electrochemical Characterization on Au(111) surface

Abstract: In the memory of Janez (Janko) Jamnik, my doctoral advisor who taught me that everything can be done and built if there is a vision and a will. AbstractSeveral new electroactive diquinone and dihydroquinone derivatives of calix [4]arene bearing anchor functional groups were designed, synthesized and characterized. A method for selective protection of the hydroquinone -OH groups with trimethylsilyl groups (TMS) either on lower-rim or on upper-rim was developed. Four selected molecules -with sulfide anchor group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Recently, efforts to identify promising high-performance positive electrode materials have been extended to metal-free organic materials with redox-active sites on their surfaces, such as conducting polymers and quinone molecules. In addition to their potential for kinetic performance, organic materials are attractive because they can reduce the costs of electrochemical energy storage by replacing conventional transition metal oxides with abundant carbon materials. Specifically, the potential of conducting polymers and redox-active quinone derivatives , as organic positive electrodes in lithium-ion batteries and catholytes in redox-flow batteries has been investigated intensively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, efforts to identify promising high-performance positive electrode materials have been extended to metal-free organic materials with redox-active sites on their surfaces, such as conducting polymers and quinone molecules. In addition to their potential for kinetic performance, organic materials are attractive because they can reduce the costs of electrochemical energy storage by replacing conventional transition metal oxides with abundant carbon materials. Specifically, the potential of conducting polymers and redox-active quinone derivatives , as organic positive electrodes in lithium-ion batteries and catholytes in redox-flow batteries has been investigated intensively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts to identify promising high-performance positive electrode materials have been extended to metal-free organic materials with redox-active sites on their surfaces, such as conducting polymers and quinone molecules. In addition to their potential for kinetic performance, organic materials are attractive because they can reduce the costs of electrochemical energy storage by replacing conventional transition metal oxides with abundant carbon materials. Specifically, the potential of conducting polymers and redox-active quinone derivatives , as organic positive electrodes in lithium-ion batteries and catholytes in redox-flow batteries has been investigated intensively. For instance, composites of conducting polymers (e.g., polypyrrole and polyaniline) coated on materials such as LiFePO 4 and carbon nanotubes have been suggested as promising positive electrodes with significantly enhanced electronic conductivities and electrochemical activities. , Abruña and co-workers suggested that yolk–shell structures, consisting of sulfur coated with polyaniline and incorporating an internal void space within the shell, could accommodate the volume expansion of sulfur occurring during repeated lithiation/delithiation processes in lithium–sulfur batteries .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the usual suite of characterisation techniques, crystals of appropriate quality for a single Table 1 with the hydrogen bonding polymer shown in Figure 3. The chemical reduction of quinone calixarenes has been reported using aqueous sodium dithionite, 18 and sodium borohydride. 19 Here we chose to use N,N-diethylhydroxylamine (DEH), which has been reported to reduced quinones, 16 to reduce Q to the dihydroquinone QR, to simplify the isolation of the product.…”
Section: Ligand Synthesis and Characterizationmentioning
confidence: 99%
“…Hydrogen bonding geometrical details are listed in Table 1 with the hydrogen bonding polymer shown in Figure 3. The chemical reduction of quinone calixarenes has been reported using aqueous sodium dithionite, 18 and sodium borohydride. 19 Here we chose to use N,N-diethylhydroxylamine (DEH), which has been reported to reduced quinones, 16 to reduce Q to the dihydroquinone QR, to simplify the isolation of the product.…”
Section: Ligand Synthesis and Characterizationmentioning
confidence: 99%